Cooperative adaptive driving for platooning autonomous self driving based on edge computing - Chang, Ben-Jye; Hwang, Ren-Hung; Tsai,Yueh-Lin; Yu, Bo-Han; Liang, Ying-Hsin (Zielona Góra: Uniwersytet Zielonogórski)
Cooperative adaptive cruise control (CACC) for human and autonomous self-driving aims to achieve active safe driving that avoids vehicle accidents or traffic jam by exchanging the road traffic information (e.g., traffic flow, traffic density, velocity variation, etc.) among neighbor vehicles. However, in CACC, the butterfly effect is encountered while exhibiting asynchronous brakes that easily lead to backward shock-waves and are difficult to remove. Several critical issues should be addressed in CACC, including (i) difficulties with adaptive steering of the inter-vehicle distances among neighbor vehicles and the vehicle speed, (ii) the butterfly effect, (iii) unstable vehicle traffic flow, etc.
Keywords: mobile edge computing; active safe driving; cooperative platoon driving; cooperative adaptive cruise control